Faktor Yang Berhubungan Dengan Kelelahan Kerja Pada Perawat Di RSUD Nene Mallomo Kabupaten Sidrap - Reny Angriani Azis; Arni Rizqiani Rusydi; Muhammad Khidri Alwi (Window of Public Health Journal, 2026)
Work fatigue is a common problem among healthcare workers and can affect their performance and safety. Data shows that most nurses in Indonesia experience work stress due to high workloads and limited rest periods. This study aims to determine the factors associated with work fatigue among nurses in the inpatient ward of Nene Mallomo Pangkajene Hospital, Sidenreng Rappang Regency, in 2023. This study used a quantitative, cross-sectional design. The sample size was 79 nurses, determined using the Slovin formula. Data analysis was performed using the chi-square test to assess relationships among variables. The results showed a relationship between work shifts and work fatigue (p = 0.000), while there was no relationship between workload and work fatigue (p = 0.813). This study concludes that work shifts are associated with work fatigue among nurses, whereas workload is not. Therefore, it is recommended that nurses make optimal use of rest periods, and hospitals should pay attention to work scheduling arrangements to reduce the risk of work fatigue.